2008
DOI: 10.1007/s00425-008-0856-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of silenced plants in allelopathy bioassays: a novel approach

Abstract: Volatile phytohormones or other chemicals can aVect processes in distal plant parts but may also inXuence neighboring plants, and thereby function allelopathically. While this hypothesis has been widely discussed, rigorous tests are lacking. Transgenic plants, silenced in the production of an emitted chemical, are ideal tools to test the hypothesis that the release of a chemical can negatively inXuence the growth of neighbors (allelopathy). We used isogenic wild type (WT) and genetically transformed plants tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However, our results could be strengthened by comparisons of A. adenophora litter to litter from native plants in the invader's nonnative range in both pots and Petri dish experiments. Also, Inderjit et al (2009) suggested the use of ''silenced'' plants to acquire conclusive evidence that the release of chemicals does matter in plant-plant interactions, but silencing a perennial plant for the production of more than one chemical may be a significant challenge and performing field experiments with silenced plants is yet another challenge. Perhaps the best way to demonstrate the role of VOCs produced by A. adenophora VOCs in the field will be through manipulative field studies that discriminate the effects of VOCs from those of competitors, pathogens, and herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results could be strengthened by comparisons of A. adenophora litter to litter from native plants in the invader's nonnative range in both pots and Petri dish experiments. Also, Inderjit et al (2009) suggested the use of ''silenced'' plants to acquire conclusive evidence that the release of chemicals does matter in plant-plant interactions, but silencing a perennial plant for the production of more than one chemical may be a significant challenge and performing field experiments with silenced plants is yet another challenge. Perhaps the best way to demonstrate the role of VOCs produced by A. adenophora VOCs in the field will be through manipulative field studies that discriminate the effects of VOCs from those of competitors, pathogens, and herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…) and allelopathic to plant competitors (Karban ; Inderjit et al . ). These same volatiles attract the predators and parasites of herbivores that can decrease levels of damage inflicted by herbivory (Dicke & Sabelis ; Turlings et al .…”
Section: Introductionmentioning
confidence: 97%
“…For example, volatile emissions protect plants from heat and oxidative stresses (Loreto & Velikova 2001;Behnke et al 2007). The volatiles released by herbivory are often directly repellent to herbivores (Bernasconi et al 1998;De Moraes et al 2001) and allelopathic to plant competitors Inderjit et al 2009). These same volatiles attract the predators and parasites of herbivores that can decrease levels of damage inflicted by herbivory (Dicke & Sabelis 1988;Turlings et al 1990;Thaler 1999;Kessler & Baldwin 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these assays performed under laboratory conditions, field experiments (Karban et al 2000;Dolch and Tscharntke 2000;Heil and Silva Bueno 2007) and bioassays using transgenic plants unable to release ('mute emitters') or perceive ('deaf receivers') the key volatile signals Paschold et al 2006;Inderjit et al 2009) have demonstrated that VOCs can act as interplant signals in nature. Belowground, original experimental devices have been designed to study the roles played by root-emitted VOCs in biotic interactions.…”
Section: Technical Challenges and Perspectivesmentioning
confidence: 99%